Online Shopping Purchase Patterns with Special Reference to Demographic and Informational Influence - Rani, T. Suchitra; Sripathi, Nishchala (International Journal of Social Sciences and Management, 2017)
While many Indian feel good to see, touch and go round the retail outlets for shopping but however, Internet has transformed many aspects of life. For some services like booking ticket and travel plans this has definitely become the most preferred source of purchase due to convenience. This paper is an attempt to bring out different aspects of this trend of online buying behavior which has picked up since almost 15 years, it highlight the factors influencing the online buying decision along with the negative factors which deter the consumer to go online purchase. Further, the study focuses on how the demographic factors influence the online buying decision along with the informational sources that influence the choice of websites. From the study it was found that clothes, footwear and accessories are the most purchase online, while the factors that interests the online shopper was found to be discounts and the negative motivation was due to poor quality of product and fake product. Int. J. Soc. Sc. Manage. Vol. 4, Issue-1: 38-43